PROFIL MODEL PEMBELAJARAN SOFT-SKILL PADA SMK BIDANG EKONOMI DI SURAKARTA ( kajian aspek Apa; Mengapa; dan Bagaimana ) - Budi Sutrisno (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The purpose of this research was to describe the profile of soft skill teaching model in the economic and business vocational school (SMK) especially in productive subject that appropriate with industry needs. This was an qualitative research with the ethnographic approach. The data collection methods were interview, observation, documentation, and closed questionnaire. The source persons were vocational principals in Surakarta and CEO of some industries in Surakarta. The data analysis conducted by using the interactive pattern of analysis components. The research indicated that vocational schools in Surakarta needed to develop network among schools. However, while the private vocational school only had local network, the state vocational schools had wider network such as having collaboration with industry from Japan, Korea, and some countries from the Southeast Asia. The collaboration with the industry must cover the curriculum needs that had been adopted by the vocational school. The curriculum must include hard skill and soft skill. Hard skill must consist of knowledge (25%) and skill (35%). Whereas soft skill consist of character (24%) and physical condition (16%). There are two conclusion of this study. Firstly, the soft skill teaching in state vocational school had already integrated with teaching and learning activity. While, secondly, in the private vocational school still disintegrated with teaching and learning activity. Most private vocational school integrated soft skill with extra activities in school. Kata Kunci: Profil, Model, Pembelajaran, Soft-Skill, SMK